Analisis Pengukuran Kualitas Aplikasi Satu Kemenkeu pada KPP Madya Palembang Menggunakan Technology Readiness Acceptance Model (TRAM) - Mukarromah, Dilla; Herdiansyah, Muhammad Izman (Program Studi Teknik Informatika Universitas Pamulang, 2024)
Technology in Indonesia has been applied in various fields, both in education, government, health and other community activities. At KPP Madya Palembang, Information Technology has been applied in various activities and services, one of which is on the website of Satu Kemenkeu. On the Satu Kemenkeu website, it is a new system implemented by KPP Madya Palembang. Satu Kemenkeu is a new system that has never been analyzed. In Satu Kemenkeu, various problems were found such as usability, Interface, Home section that cannot be fully functioned, some features cannot be accessed. Based on the problems found, an analysis is needed to measure the quality of Satu Kemenkeu. Measurement of quality in the category of user readiness and acceptance at Satu Kemenkeu to determine the readiness of users to accept the technology. The model used in readiness and acceptance is the Technology Readiness Acceptance Model (TRAM). This study uses 7 variables in TRAM, namely Optimism, Innovativeness, Discomfort, Insecurity, Perceived Usefulness, perceived ease of use, intention to use. This study distributed questionnaires to 114 employees of KPP Madya Palembang as users of Satu Kemenkeu. Then, for data analysis used SEM-PLS with SmartPLS Tools. The results of this study from 10 hypotheses there are 4 hypotheses accepted and 6 rejected. The overall results show the quality of one ministry of finance using TRAM of 71.8%, this shows that the quality of the one ministry of finance application can be used and accepted by users.